The castle at Gradišče above Draga A Spanheim stronghold on the northwestern border of their domain? - Gaspari, Andrej; Nadbath, Barbara; Nabergoj, Tomaž (Arheološki vestnik, 2008)
The peak of Gradišče above the village of Draga reveals the ruins of a High Medieval stronghold, of which we can identify the remains of a high strong house or shell castle with a double keep, bailey and a small secondary building. The stronghold is a fine example of the exploitation of favourable geomorphologic and strategic conditions, which in this case provided effective control over the routes between Goričane and the confluence of the Poljanska Sora and the Selška Sora Rivers, as well as visual communication with the castle of Stari grad at Smlednik. The analysis of metal objects from this site in the collections of the National Museum of Slovenia enabled the stronghold to be approximately dated to the 12th/13th centuries. Its posi-tion on the boundary between the domains of the Bishop of Freising, the Counts of Andechs, and the Spanheims, the Dukes of Carinthia, leads to the assumption that the stronghold was in the possession of Spanheim ministerials, the lords of Sora, who are mentioned in literary sources between the mid 12th and the beginning of the 13th centuries. The peak of Gradišče above the village of Draga reveals the ruins of a High Medieval stronghold, of which we can identify the remains of a high strong house or shell castle with a double keep, bailey and a small secondary building. The stronghold is a fine example of the exploitation of favourable geomorphologic and strategic conditions, which in this case provided effective control over the routes between Goričane and the confluence of the Poljanska Sora and the Selška Sora Rivers, as well as visual communication with the castle of Stari grad at Smlednik. The analysis of metal objects from this site in the collections of the National Museum of Slovenia enabled the stronghold to be approximately dated to the 12th/13th centuries. Its posi-tion on the boundary between the domains of the Bishop of Freising, the Counts of Andechs, and the Spanheims, the Dukes of Carinthia, leads to the assumption that the stronghold was in the possession of Spanheim ministerials, the lords of Sora, who are mentioned in literary sources between the mid 12th and the beginning of the 13th centuries.